PREDIKSI PENGGUNAAN LAHAN SAWAH DI KOTA PAYAKUMBUH MENGGUNAKAN METODE CELLULAR AUTOMATA - Farashanda, Dwina; ., Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Payakumbuh City is a developing region in West Sumatra. The area has undergone changes in land use due to an increase in the population, leading to a reduction in rice fields as they are converted into residential areas. The aim of this research is to identify the characteristics of changes in rice field land use in Payakumbuh and predict changes in rice field land use by the year 2032. The study utilizes SPOT images from 2019, 2019, and 2022. Driving factors inputted into LanduseSim include main road accessibility, secondary road accessibility, existing settlements, and rivers. The analysis results indicate a consistent decline in rice field land use in Payakumbuh. There has been a shift in the function of rice fields, with the most significant change being the conversion of rice fields into residential areas. Based on the predicted analysis of rice field land use from 2022 to 2032, only residential areas experience changes, with an additional area of 283.43 hectares. The results of the land change prediction in 2032 this can be used as a planning input to focus more on regional imbalances in border area.